MARKET ANALYSIS OF SERBIAS RASPBERRY SECTOR AND CLUSTER DEVELOPMENT INITIATIVES - Parausić, Vesna; Simeunović, Ivana (Economics of Agriculture, 2016)
Authors analyze competitive strength and weakness of raspberry producers in Serbia and propose key prerequisites of which fulflling will depend develop of successful cluster initiative in Serbian raspberry sector. The research results indicate that Serbian raspberry growers can develop successful cluster and they can keep leading position in the global market of raspberries, only with following many assumptions, like: (a) better organized marketing channel through the vertically and horizontal integration of all actors in this sector,(b) strengthening specialized cooperatives for raspberry production and associations of raspberry growers, and in the future setting up of producer organisations and associations; (c) inclusion of producers of other berries and producers of processed berries; (d) introducing innovations, scientifc knowledge, and research and development in production, processing, packing, logistics, export of raspberries, etc. An analysis is based on case study in Šumadija and Western Serbia region, which is major region in raspberry production in Serbia.